Intergenerational transmission of health disparities among Turkish-origin immigrants in Germany: study protocol of a multi-centric cohort study (BaBi-stress and BaBeK study) - Jacob Spallek; Laura Scholaske; Medlin Kurt; Denise Lindner-Matthes; Sonja Entringer (BMC, 2020)
Abstract Background Immigrants in Germany exhibit higher levels of social disadvantage when compared to the non-immigrated population. Turkish-origin immigrants constitute an important immigrant group in Germany and show disparities in some health domains that are evident from birth onwards. Several studies have shown the mechanisms by which social disadvantage is biologically embedded to affect health over the lifespan. Relatively little, however, is still known about if and how the maternal social situation is transmitted to the next generation. This study therefore aims to analyse the effects of maternal socioeconomic status and migration status on stress-related maternal-placental-fetal (MPF) biological processes during pregnancy on infant birth and health outcomes. Methods This longitudinal cohort study of N = 144 child-mother dyads is located at two study sites in Germany and includes pregnant women of Turkish origin living in Germany as well as pregnant German women. During pregnancy, MPF stress biology markers from maternal blood and saliva samples, maternal socio-economic and migration-related information, medical risk variables and psychological well-being are assessed. After birth, infant anthropometric measures and developmental outcomes are assessed. The same measures will be assessed in and compared to Turkish pregnant women based on a collaboration with BABIP study in Istanbul. Discussion This is the first study on intergenerational transmission of health disparities in Germany with a focus on women of Turkish-origin. The study faces similar risks of bias as other birth cohorts do. The study has implemented various measures, e.g. culturally sensitive recruitment strategies, attempt to recruit and follow-up as many pregnant women as possible independent of their social or cultural background. Nevertheless, the response rate among lower-educated families is lower. The possibility to compare results with a cohort from Turkey is a strength of this study. However, starting at different times and with slightly different recruitment strategies and designs may result in cohort effects and may affect comparability of the sub-cohorts. Trial registration N.A. (Observational study, no clinical trial, no interventions on human participants).